Convergencia económica en la OPEP: 1970-2017; Economic convergence in OPEC: 1970-2017 - Ángel Enrique Martínez Gámez (Revista de Métodos Cuantitativos para la Economía y la Empresa, 2021)
– Studies in economic growth have focused on the convergence hypothesis for regions, territories and groups of countries. The main idea is that on the long run, the poorer regions would catch up to the richer in terms of Gross Domestic Product Per Capita. This paper analyses the economic convergence in the Organization of Petroleum Exporting Countries (OPEC), not considered in studies related to the organization, which offers an expanded view on the matter. Utilizing an estimation and panel data analysis for the period 1970-2017, it indicates whether the gaps between countries belonging to the block have tended to be reduced or widened, and for this, an econometric model based on the literature is developed, with different equations, periods, variables and set of countries within the OPEC. The results mainly show convergence and the formation of convergence clubs between these economies, and a growth dynamic determined by human capital and physical capital.
Keywords: C23; F43; O47; 330; data panel models; economic growth; empirical convergence studies